A Systematic Literature Review on Enhancing the Success of Independent Curriculum through Brain-Based Learning Innovation Implementation - Dimas Febriansyah Krisna Dwiputra; Waliyyatu Azzahra; Fahmi Nugraha Heryanto (Universitas Muhammadiyah Surakarta, 2023)
Brain-based Learning has been recognized for its potential to foster creative and innovative pedagogical approaches. Despite this, the relevance and potential impact of this model with the independent curriculum remains relatively unexplored by previous research. This study seeks to address this gap by investigating and analyzing the relevance and benefits of integrating Brain-based Learning within the independent curriculum framework in Indonesia. Employing a Systematic Literature Review referred to the 2020 PRISMA guidelines, we obtained 2013 articles from Scopus and Google Scholar databases but only 48 articles met the eligibility criteria for further analysis using the meta-synthetic analysis method. Results indicate the relevance between Brain-based Learning and the principles of differentiated learning inherent to the independent curriculum. By focusing on the natural system of the brain, Brain-based Learning enhances the efficacy of the curriculum, yielding enjoyable, meaningful, and beneficial learning experiences for students. This underscores the potential of Brain-based Learning as a driving force for the success of the independent curriculum in overcoming educational challenges in Indonesia.